Attenuation of Thrombolysis-induced Increase of Plasminogen Activator Inhibitor-1 by Intravenous Enalaprilat - Hirschl, Michael M.; Wagner, Andreas; Gwechenberger, Marianne; Herkner, Harald; Müllner, Marcus; Woisetschläger, Christian; Laggner, Anton N. (Thrombosis and Haemostasis, 1998)
We examined the effect of intravenous enalaprilat on the course of PAI-1 plasma levels in 23 patients with acute myocardial infarction undergoing thrombolytic therapy. All patients received 100 mg aspirin, 1000 IU/h heparin, thrombolysis with 100 mg rt-PA within 90 min, and betablockers. Eleven out of 23 patients received 5 mg enalaprilat intravenously prior to thrombolysis. Blood samples for determination of PAI-1 plasma levels were collected on admission, 2, 4, 6, 12, and 24 h after thrombolysis. PAI-1 plasma levels in patients receiving enalaprilat were similar to those of the control patients before thrombolysis (5 ng/ml, 95% confidence interval: 2-10 vs. 7 ng/ml, 95% confidence interval: 2-10; p = 0.5). The PAI-1AUC was 9 ng/ml/h (95% confidence interval: 5-10) in the enalaprilat group and 19 ng/ml/h (95% confidence interval: 13-26) in the control group (p = 0.0006). The maximum difference was observed 6 h after thrombolysis (enalaprilat: 13 ng/ml, 95% confidence interval: 5-25, control: 42 ng/ml, 95% confidence interval: 18-55; p = 0.003).Our study clearly demonstrates that application of intravenous enalaprilat prior to thrombolysis attenuates the thrombolysis-related increase of PAI-1. This finding may suggest a possible therapeutic approach to influence the fibrinolytic system in patients with acute myocardial infarction after thrombolysis.